Pricing for profit how to command higher prices for your products and services - Furtwengler, Dale (AMACOM, 2010)
Few businesses are compensated well for the value they provide.
Includes bibliographical references. - Print version record
Keywords: Pricing; Markup; Marketing; Prix; Fixation; Marge bénéficiaire; marketing